Road mitigation is a demographic filter for grizzly bears. (21st November 2017) - Ford, Adam T.; Barrueto, Mirjam; Clevenger, Anthony P.
ABSTRACT: Crossing structures (i.e., underpasses and overpasses) are becoming a widespread approach to promote movement of wildlife across roads. Studies have shown that species select for different crossing structure designs, yet little is known about intraspecific variation (i.e., differences among demographic classes) in crossing structure preference. Using data on grizzly bear ( Ursus arctos ) movement in Banff National Park (AB, Canada), we focused on selection by family groups (adult females travelling with young) and singleton (adult male or female) bears for 5 crossing structure designs distributed among 44 sites. Using data from the world's longest running monitoring program (1997–2014) on wildlife crossing structure use, we created an economic model to estimate demographic‐specific cost‐effectiveness for each crossing structure design. We found that all grizzly bears selected larger and more open structures (overpasses and open‐span bridges). Use of these structures has generally increased with time at a rate that exceeds estimates of population growth. Family groups were more selective than singletons and strongly selected overpasses. In spite of singletons' selection for overpasses and open‐span bridges, box culverts were comparable in cost‐effectiveness. Our results suggest that structure designs targeting the selection of grizzly bear family groups are effective at restoring population connectivity, but a systematic approach to designing highway mitigation also would consider the role of lesser used structures in reducing intraspecific predation and multispecies connectivity targets. © 2017 The Wildlife Society. Abstract : Our objective was to determine how reproductive and group status of grizzly bears influences their use of wildlife crossing structures—passages built under and over highways to facilitate animal movement. Grizzly bears use different types of structures depending on their reproductive status, with adult females and young selecting overpasses, and single animals using a greater diversity of crossing structure designs.